Estimation of inertia demand in power systems considering wind power virtual inertia - Hongchun SHU; Haifei DONG; Jing CHEN; Guangxue WANG; Xi WANG; Botao SHI (International Journal of Electrical Power & Energy Systems)
The high proportion of renewable energy integrated into the grid through numerous power electronic devices has reduced the overall system inertia level and operational stability and caused poor disturbance resistance. Considering the frequency stability of power systems, this study proposes an inertia demand assessment method for renewable energy power systems. The proposed method evaluates the inertia requirements of a power system at a certain level of renewable energy penetration to ensure that the system’s operational frequency stays with the safety boundaries after a system disturbance instead of increasing the inertia level to 100% synchronous machines. This can meet the inertia requirements of a power system while ensuring frequency safety, thus reducing the system’s inertia reserves. In addition, the inertia demand assessment considers the virtual inertia of renewable energy. The proposed method is verified using an IEEE 39 bus time-domain simulation model constructed in the RTLAB simulation environment. The inertia requirements are estimated under different wind power penetration levels of 20%, 40%, and 60%. The proposed method is also compared with the traditional method that uses only the fmin constraint to demonstrate the effectiveness and accuracy of the proposed method in estimating inertia requirements of wind-integrated power systems with virtual inertia. The proposed method is further validated using actual grid data from Yunnan under two operational scenarios corresponding to the wet and dry seasons. The results show that by using both the RoCoFmax and fmin constraints, the proposed method can achieve a more accurate assessment of the inertia level in large-scale wind-integrated power systems with virtual inertia compared to the methods that use only one constraint.